Pengetahuan Dan Sikap Ibu Tentang Makanan Kariogenik Dengan Jumlah Karies Gigi - Anggiana Sara Yuningtyas; Siti Sulastri; Almujadi Almujadi (Journal of Oral Health Care, 2017)
Dental caries or tooth decay is one of the dental and oral health problems that are common in today's society. Elementary school children including vulnerable age who need to get attention for that period are deciduous teeth and permanent teeth simultaneously in the oral cavity are more susceptible to caries. Carbohydrates such as sucrose can cause dental caries, known as cariogenic foods in the role of parents, especially mothers to feed children mainly occurs during the process of food preparation. Action decision-making by the mother in the provision of good food is strongly influenced by maternal psychological readiness level of knowledge and attitudes among mothers. The habit of eating sweet foods influential in the formation of dental caries in children, which in turn also affects the number of caries. The purpose of this study is to describe the mother's knowledge and attitudes about food cariogenic by the number of dental caries Elementary School third grade students Godean 1. The subjects of the research arestudents and students’s mother of Elementary School third grade students Godean 1. This research uses descriptive quantitative method, then the results are presented in tables and percentages. The results showed the knowledge and attitudes of mothers included in both categories with a percentage of 41.7% of mother's knowledge and attitudes of mothers 46.7% with little amount of dental caries is 1-2 caries or 46.7% in the Elementary School third grade students Godean 1. The conclusion that can be drawn from this research, knowledge and attitude of mother about cariogenic food good with little number of child caries.